Bulletin of FVR "Sermons" : vol. 8 : moving ahead : daang tama? at/o daang tuwid? = right path? and/or straight path? - Ramos, Fidel V. ([Manila, Philippines] : Ramos Peace and Development Foundation, 2013)
To achieve the right path, the straight path must be enhanced by clear vision, people empowerment, inclusiveness, outreach, performance, and competitiveness.
Chapter I. Moving the nation ahead towards our better future -- Chapter II. Striving for excellence through people empowerment -- Chapter III. Harmonizing efforts towards sustainable peace -- Chapter IV. Integrating grassroots democracy to address social justice and equity -- Chapter V. Conquering poverty to win inclusive development
"Selected articles from the Sunday column of former President Fidel V. Ramos in the Manila Bulletin."-- Cover
Includes index.
Keywords: ASIA -- FOREIGN RELATIONS